BCCIP binds to and activates its promoter in a YY1‐dependent fashion in HCT116 cells. (4th July 2018) - Sui, Yi; Li, Fuqiang; Wu, Tingting; Ding, Jian; Lu, Zeming; Wang, Lingyao; Yang, Yang; Wang, Fei; Zhao, Linhong; Zhu, Huihui; Wei, Tao; Jin, Jingji; et al.
Abstract : The restriction of Yin Yang 1 (YY1) at BRCA2 and CDKN1A/p21‐interacting protein (BCCIP) transcriptional start site (TSS) proximal region in several human cancer cell lines was found by analyzation of ChIP‐Seq database from UCSC Genome Browser (http://genome.ucsc.edu ). However, whether the stabilization of YY1 by BCCIP impacts its recruitment in the BCCIP promoter region is unclear. Here, we present evidence that transcriptional regulation of YY1 on BCCIP is closely related to YY1 stability in HCT116 human colon cancer cells. YY1 stabilization was in turn regulated by BCCIP, suggesting the existence of a BCCIP–YY1 feedback loop in regulating BCCIP transcription by the YY1. Overexpression of BCCIP stabilized YY1 while knockdown of BCCIP reduced YY1 protein level. In addition, direct interaction between YY1 and BCCIP was confirmed by coimmunoprecipitation approach. Also, the N‐terminus region of BCCIP, including the internal conserved domain (ICD), was responsible for binding with the amino acid 146–270 of YY1. More importantly, YY1 stability was related to the BCCIP/ICD domain‐mediated YY1 ubiquitination pathway. Moreover, a limited BCCIP promoter region containing YY1 binding site (CCGCCATC) was tightly associated with the pGL4‐BCCIP‐Luc luciferase activity. In ChIP assays, shBCCIP lentiviral‐mediated YY1 instability decreased recruitment of the YY1 at BCCIP TSS proximal region, which could not be restored by YY1 overexpression. Furthermore, knockdown of YY1 inhibited the binding of BCCIP itself at BCCIP promoter region proximal to TSS, demonstrating that transcriptional regulation of the YY1 on BCCIP can be modulated by BCCIP itself in a YY1‐dependent fashion. Abstract : Increased exogenous BRCA2 and CDKN1A/p21‐interacting protein (BCCIP) stabilizes Yin Yang 1 (YY1) protein by directly binding to it and promoting the recruitment of BCCIP/YY1 to transcriptional start site (TSS) proximal region of BCCIP, further activating the BCCIP transcription. Conversely, decreased endogenous BCCIP is unable to bind to and stabilize YY1, thus the BCCIP/YY1 cannot be recruited to BCCIP promoter region, and the proteasome‐mediated degradation pathway of YY1 was increased.